THE IMPORTANCE OF THE ACTIONS OF THE PUBLIC DEFENDER AS INSTRUMENTS FOR THE ENFORCEMENT OF THE RIGHTS OF THE PERSON WITH DISABILITY IN TIMES OF COVID-19 - Leite, Flávia Piva Almeida; Oliveira, Leonardo Lucas Silva [UNESP] (My University, 2022)
Objective: The objective of this article is to understand issues concerning the defense of the rights of people with disabilities in the midst of the pandemic reality caused by COVID-19, under the perspective of the Public Defender's Office. Methodology: The methodology applied in this study has, as a method of procedure, bibliographic and documentary analysis, and, with regard to the approach method, the deductive is used. It is noteworthy that the present research is classified as a qualitative exploratory. Background: Covid-19 has negatively affected a relatively large number of people, especially the most vulnerable groups in society, such as people with disabilities. Results: It can be concluded that, in view of the current reality, there is a need for society in institutions and agents that seek measures that bring protection and security to overcome the current factual context with the least possible damage, being the work of public defender, at this moment, fundamental for the survival of thousands of people. Contribution: The main contribution of the work lies in the fact that it demonstrates the importance and responsibility of the institutions, especially the Public Defender's Office, which has the legitimacy to protect the rights of people with disabilities and to develop health policies that minimize the negative effects caused by the current pandemic towards those people.
A IMPORTÂNCIA DAS ATUAÇÕES DA DEFENSORIA PÚBLICA COMO INSTRUMENTOS DE EFETIVAÇÃO DOS DIREITOS DA PESSOA COM DEFICIÊNCIA EM TEMPOS DE COVID-19
Keywords: Defender; Disability; Pandemic; People; Rights